Management of Menstrual Disorder in Adolescent Girls with Intellectual Disabilities: A Blessing or a Curse? - Abu Ishak Nurkhairulnisa; Kah Teik Chew; Ani Amelia Zainudin; Pei Shan Lim; Mohamad Nasir Shafiee; Nirmala Kampan; Wan Salwina Wan Ismail; Sonia Grover; Abdul Ghani Nur Azurah (Obstetrics and Gynecology International)
Objective. This study aims to describe the menstrual pattern and menstrual care of girls with intellectual disabilities and to evaluate the impact of menstruation and awareness of parents/guardians on girls with intellectual disabilities. Methodology. Parents/guardians of girls aged 9–17 years with known intellectual disabilities who attended a scheduled public forum and Paediatrics and Adolescent Gynaecology Clinic (PAC) were recruited in a questionnaire-based study. Results. A total of 123 parents/guardians with a mean age of 41.83 ± 5.45 years completed the questionnaire. The mean age of girls with intellectual disabilities was 12.28 ± 2.78 years, and the mean menarcheal age was 11.12 ± 1.76 years. Only 53 (43.1%) parents/guardians were aware of availability of menstrual suppression. Parents/guardians with lower family income (OR = 0.00; 95% CI = 0.00–0.20), unable to manage menses (OR = 0.03; 95% CI = 0.00–0.61), and moderate severity of menses (OR = 0.01; 95% CI = 0.00–1.21), were associated with seeking medical help on menstrual suppression. The factors associated with parents/guardians requesting for sterilization were lower family income (OR = 0.02; 95% CI = 0.00–0.36) and concern about sexual abuse (OR = 0.25; 95% CI = 0.06–0.39). Conclusion. Menstrual pattern in girls with intellectual disabilities is similar to those without disabilities. Parents/guardians’ knowledge and awareness on menstrual suppression were still lacking.